Amylase gene expression patterns in Helicoverpa armigera upon feeding on a range of host plants - Kotkar, Hemlata M.; Bhide, Amey J.; Gupta, Vidya S.; Giri, Ashok P. (Gene, 2012)
Expression of two amylase genes (HaAmy1 and HaAmy2) was studied in Helicoverpa armigera (Hubner; Lepidoptera: Noctuidae) feeding on different host plants and during larval development. Alignment of HaAmy1 and HaAmy2 with other insect amylases shows similarities with known Lepidopteran amylase transcripts. H. armigera amylase gene expression is influenced by the availability of reducing sugars, sucrose and starch content of host plants and further correlates to the pool of reducing sugars in the gut and haemolymph of larvae. HaAmy1 and HaAmy2 during larval development on two host plants viz., maize (cereal) and marigold (ornamental) showed their relative difference. Results support the view that when host plants differ in their macronutrients, relationships of enzymes and substrates are flexible. The present work highlights the distribution of HaAmy1 and HaAmy2 (i) during various stages of insect development (second, fourth and sixth instar, pupa, adult and egg), (ii) in various tissues viz., head, haemolymph, fat body, integument and whole larval body of H. armigera feeding on artificial diet and (iii) in three gut regions of larvae fed on various diets. Complexity in expression of amylase genes suggests existence of mechanisms involved to detect nutrient balance required for avoiding fitness costs and focus their importance in insect nutrition. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Diets; Digestive amylase; Gene expression; Helicoverpa armigera; Nutrition